Room temperature ferromagnetism in undoped and Fe doped ZnO nanorods: microwave-assisted synthesis - Limaye, Mukta V.; Singh, Shashi B.; Das, Raja; Poddar, Pankaj; Kulkarni, Sulabha K. (Journal of Solid State Chemistry, 2011)
One-dimensional (1D) undoped and Fe doped ZnO nanorods of average length similar to 1 mu m and diameter similar to 50 nm have been obtained using a microwave-assisted synthesis. The magnetization (M) and coercivity (H-c) value obtained for undoped ZnO nanorods at room temperature is similar to 5 X 10(-3) emu/g and similar to 150 Oe, respectively. The Fe doped ZnO samples show significant changes in M -H loop with increasing doping concentration. Both undoped and Fe doped ZnO nanorods exhibit a Curie transition temperature (T-c) above 390 K. Electron spin resonance and Mossbauer spectra indicate the presence of ferric ions. The origin of ferromagnetism in undoped ZnO nanorods is attributed to localized electron spin moments resulting from surface defects/vacancies, where as in Fe doped samples is explained by F center exchange mechanism. (C) 2010 Published by Elsevier Inc.
Keywords: Diluted magnetic semiconductors; Nanostructures; ZnO

Self-assembled vertically aligned gold nanorod super-lattices for ultra-high sensitive detection of molecules - Apte, Amey; Bhaskar, Prashant; Das, Raja; Chaturvedi, Smita; Poddar, Pankaj; Kulkarni, Sulabha (Nano Research, 2015)
We show that self-assembled vertically aligned gold nanorod (VA-GNRs) superlattices can serve as probes or substrates for ultra-high sensitive detection of various molecules. D-glucose and 2,4,6-trinitrotoluene (TNT) have been chosen as model systems due to their very low Raman cross-sections (5.6 x 10(-30) cm(2).molecule(-1).sr(-1) for D-glucose and 4.9 x 10(-31) cm(2). molecule(-1).sr(-1) for TNT) to show that the VA-GNR superlattice assembly offers as low as yoctomole sensitivity. Our experiment on mixed samples of bovine serum albumin (BSA) and D-glucose solutions demonstrate sensitivity for the latter, and the possible extension to real samples. Self-assembled superlattices of VA-GNRs were achieved on a silicon wafer by depositing a drop of solvent containing the GNRs and subsequent solvent evaporation in ambient conditions. An additional advantage of the VA-GNR monolayers is their extremely high reproducible morphology accompanied by ultrahigh sensitivity which will be useful in many fields where a very small amount of analyte is available. Moreover the assembly can be reused a number of times after removing the already present molecules. The method of obtaining VA-GNRs is simple, inexpensive and reproducible. With the help of simulations of monolayers and multilayers it has been shown that superlattices can achieve better sensitivity than monolayer assembly of VA-GNRs.
Keywords: Nanostructures; Raman spectroscopy; self-assemblies; sensors; superlattices